2021
DOI: 10.1038/s41598-020-79775-0
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation resistance mechanism of the CoCrFeMnNi equiatomic high-entropy alloy

Abstract: When face-centered cubic (FCC) metals and alloys with low stacking fault energy (SFE) are irradiated by high-energy particles or deformed at high speed, stacking fault tetrahedra (SFTs), which are a type of vacancy cluster defect, are often formed. Therefore, SFTs were expected to form in the CoCrFeMnNi equiatomic high-entropy alloy (HEA). However, no SFT was observed in the CoCrFeMnNi HEA with high-speed plastic deformation even after annealing at 873 K. To elucidate this mechanism, the binding energy of vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It is also shown by Zhao that most interstitial dumbbells are along the [110] direction 43 , which in BCC systems, involves a sequence of rotational and translational jumps as described by Schilling 44 . Others related the high irradiation resistance of HEAs to lattice distortion and sluggish diffusion effects 45 or the difficulty of defect clustering 46 . Using electronic structure calculations as implemented in VASP code, formation, and migration energies of He were computed in the W-Ta-Cr-V system 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It is also shown by Zhao that most interstitial dumbbells are along the [110] direction 43 , which in BCC systems, involves a sequence of rotational and translational jumps as described by Schilling 44 . Others related the high irradiation resistance of HEAs to lattice distortion and sluggish diffusion effects 45 or the difficulty of defect clustering 46 . Using electronic structure calculations as implemented in VASP code, formation, and migration energies of He were computed in the W-Ta-Cr-V system 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the average binding energy of tri-vacancy in HEA is negative while tetra-vacancy binding energy is positive. Therefore, the instability of trivacancy or negative binding energy is responsible for the irradiation (ions or neutrons) resistance [84]. The irradiation induced defects in NiCoCrFe HEA were studied through MD simulations of modelled displacement cascades.…”
Section: Electromagnetic Wave Shielding Materialsmentioning
confidence: 99%
“…At high temperatures, vacancy properties are known to control RMEA performance such as the irradiation resistance, phase stability and creep deformation [ 26 , 27 , 28 , 29 ]. Thus, gaining a detailed understanding of vacancy energetics is a first important step to quantify the parameters that govern mass transport properties in these alloys.…”
Section: Introductionmentioning
confidence: 99%